Implantation of the First IMT Macular Lens in Age-Related Macular Degeneration (Literature Review) - M. M. Bikbov; O. I. Orenburkina; A. E. Babushkin (Acta Biomedica Scientifica)
This review presents the characteristics and results of clinical studies of patients with age-related macular degeneration implanted with the developed for this purpose first macular IOL – intraocular macular telescope (IMT). This lens was designed specifically for patients with the most severe or terminal form of age-related macular degeneration and is designed for monocular implantation to provide central vision while maintaining peripheral vision of the paired eye, which is important for maintaining the balance and orientation of patients. This device allows patients to see both in dynamic and static situations in the near, intermediate and far ranges. The disadvantages of this lens are a decrease in the visual field and depth of focus (which excludes its bilateral implantation), the need for a large (10–12 mm) incision for implantation, which can cause an increase in corneal astigmatism and the risk of complications, in particular, the pupillary block with an increase in intraocular pressure. There are also difficulties in the study of the fundus after its implantation to assess the small changes in the macula or to identify possible postoperative complications after cataract surgery (macular oedema, etc.). Also after the implantation of this lens, there is need for special programs of visual rehabilitation. The patient’s commitment to the rehabilitation measures for the adaptation of the central visual field of the operated eye with the peripheral vision of the second eye is crucial for success of the IMT macular telescope implantation procedure.